Hillock sizes after wet etching in silicon - Mirabella, D. A. (2009)
The formation of two- and three-dimensional hillocks is regularly observed in Si(1 1 1) steps and Si(1 0 0) during wet etching. Frequently the resulting morphology consists of hillocks scattered on a landscape of limited roughness. Recently we proposed a mean field model (MFM) in which the observed hillock-and-valley pattern is possible under steady state if hillock etching is slightly faster than valley etching. This condition implies that hillock size distributions must be an exponential decreasing function. In this work, we report a systematic study of hillock size distributions of experimental morphologies obtained under different etchant concentrations in Si(1 0 0). We found that experimental hillock size distributions are in agreement with those predicted by the MFM.